A new species of Chrysosphaerella (Chrysophyceae: Chromulinales), Chrysosphaerella rotundata sp. nov., from Finland - Skaloudova, Magda; Skaloud, Pavel (Phytotaxa, 2013)
Chrysosphaerella rotundata sp. nov. is described from a small lake in Finland. Ultrastructural morphology of C. rotundata scales is similar, even identical, to the morphology of C. brevispina scales. However, C. rotundata possesses three types of scales: scales characterized by a circular or almost circular outline were found in addition to the larger and smaller oval scales. Significant genetic differences were recognized in ITS rDNA sequences between C. rotundata and C. brevispina. Results of the molecular analyses and the observed morphological variation of scales have been discussed, clearly showing the existence of a hidden diversity within the genus Chrysosphaerella.